IMPLEMENTASI PENDIDIKAN INKLUSI DI SEKOLAH DASAR NEGERI 54 YAYASAN TAHIJA BANDA ACEH (Suatu Kajian tentang Interaksi Edukatif) - M. Hasan (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2019)
Abstract Education is a process that lasts a lifetime and is an obligation that must be fulfilled by all people, both those who have limitations and those who are normal. Such education is known as inclusive education, which is education that does not distinguish between normal humans and disabled people from all sides. The issues discussed in this paper relate to the good reasons for applying the Inclusion Pendidian in 54 Banda Aceh State Primary Schools, how education interactions are developed by schools with special needs workers and what factors support and hinder the implementation of Inclusion education at Banda Aceh 54 Primary Schools. Keywords: Implementation, Inclusive Education, Educational Interaction Abstrak Pendidikan adalah sebuah proses yang berlangsung sepanjang hayat dan merupakan kewajiban yang harus dipenuhi oleh semua orang, baik yang memiliki keterbatasan maupun yang normal. Pendidikan yang sejenis itu dikenal dengan pendidikan Inklusi, yaitu pendidikan yang tidak membedakan antara manusia yang normal dengan manusia yang cacat dari segala sisi. Permasalahan yang dibicarakan pada tulisan ini berkaitan dengan alasan baiknya penerapan pendidian Inklusi pada Sekolah Dasar Negeri 54 Banda Aceh, bagaimana interaksi edukasi yang dibangun oleh pihak sekolah dengan ABK dan faktor apa saja yang mendukung serta menghambat pelaksanaan pendidikan Inklusi pada Sekolah Dasar Negeri 54 Banda Aceh. Kata Kunci: Impelementasi, Pendidikan Inklusi, Interaksi Edukasi